(untitled) (Research, Society and Development, 2024)
The aim of this study is to detail the aspects of this violence, the characteristics of bite marks, and the strategies applicable to dental practice for identifying victims of child abuse. The methodology adopted was an integrative review, which covered articles published between 1980 and 2023 in the LiLACS, SciELO, and PubMed databases, focusing on publications in Portuguese and English. The main difficulties encountered include distortions in soft tissues and the lack of standardization in the analysis of marks, issues that have the potential to be alleviated by the use of digital techniques, such as 3D scanning and rapid prototyping. These technologies improve the accuracy of documenting the characteristics of bite marks, allowing for a more detailed and reliable assessment. The continuous training of professionals is emphasized as essential to ensure the effectiveness of forensic dentistry in identifying aggressors and protecting children in violent situations, significantly contributing to justice.